The EGFR-ADAM17 Axis in Chronic Obstructive Pulmonary Disease and Cystic Fibrosis Lung Pathology - Marta Stolarczyk; Bob J. Scholte (Mediators of Inflammation)
Chronic obstructive pulmonary disease (COPD) and cystic fibrosis (CF) share molecular mechanisms that cause the pathological symptoms they have in common. Here, we review evidence suggesting that hyperactivity of the EGFR/ADAM17 axis plays a role in the development of chronic lung disease in both CF and COPD. The ubiquitous transmembrane protease A disintegrin and metalloprotease 17 (ADAM17) forms a functional unit with the EGF receptor (EGFR), in a feedback loop interaction labeled the ADAM17/EGFR axis. In airway epithelial cells, ADAM17 sheds multiple soluble signaling proteins by proteolysis, including EGFR ligands such as amphiregulin (AREG), and proinflammatory mediators such as the interleukin 6 coreceptor (IL-6R). This activity can be enhanced by injury, toxins, and receptor-mediated external triggers. In addition to intracellular kinases, the extracellular glutathione-dependent redox potential controls ADAM17 shedding. Thus, the epithelial ADAM17/EGFR axis serves as a receptor of incoming luminal stress signals, relaying these to neighboring and underlying cells, which plays an important role in the resolution of lung injury and inflammation. We review evidence that congenital CFTR deficiency in CF and reduced CFTR activity in chronic COPD may cause enhanced ADAM17/EGFR signaling through a defect in glutathione secretion. In future studies, these complex interactions and the options for pharmaceutical interventions will be further investigated.